Discovery of Quasiperiodic Eruptions in the Tidal Disruption Event and Extreme Coronal Line Emitter AT2022upj: Implications for the QPE/TDE Fraction and a Connection to ECLEs - Joheen Chakraborty; Erin Kara; Riccardo Arcodia; Johannes Buchner; Margherita Giustini; Lorena Hernández-García; Itai Linial; Megan Masterson; Giovanni Miniutti; Andrew Mummery; Christos Panagiotou; Erwan Quintin; et al. (The Astrophysical Journal Letters)
Quasiperiodic eruptions (QPEs) are recurring soft X-ray transients emerging from the vicinity of supermassive black holes in nearby, low-mass galaxy nuclei; about 10 QPE hosts have been identified thus far. Here we report the NICER discovery of QPEs in the optically selected tidal disruption event (TDE) and extreme coronal line emitter (ECLE) AT2022upj, exhibiting a large spread in recurrence times from 0.5–3.5 days, durations from 0.3–1 days, peak luminosities from 10 ^42.5−43.0 erg s ^−1 , and erratic flare profiles. A wealth of evidence now links at least some QPEs to the newly formed accretion flows emerging from TDEs; AT2022upj is the third QPE reported in an optically discovered TDE. Marginalizing over the uncertain distributions of QPE peak luminosity, recurrence time, delay after TDE peak, and lifetime, we use the burgeoning sample to make a Bayesian estimate that the fraction of optical TDEs resulting in QPEs within 5 yr post-disruption is ${9}_{-5}^{+9}$ %. Along with AT2019qiz, AT2022upj also marks the second of the three optical TDE+X-ray QPEs showing coronal line emission, suggesting ECLEs may represent a subset of TDEs particularly efficient at forming QPEs and/or that sustained QPE X-ray emission contributes to coronal line emission in some galactic nuclei.